The pricing of retail deposits: Concentration and information - Allen, Linda; Saunders, Anthony; Udell, Gregory F (Journal of Financial Intermediation, 1991)
The traditional structure-conduct-performance (SCP) hypothesis relates concentration and the mean level of prices but ignores the dispersion of prices around their mean levels. This paper tests two hypotheses which are capable of explaining both the mean and the dispersion of elements in the pricing vector of retail banks—a concentration/collusion-based hypothesis and an asymmetric information-based hypothesis. Evidence is found that the dispersion of bank fees across banks may be due to both market structure and information reasons. The level of bank fees appears to be generally insignificantly related to concentration.